2018
DOI: 10.1007/s11082-018-1609-7
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked self-pumping and squeezing photons model in a nonlinear micro-ring resonator

Abstract: The use of a modified add-drop filter configured by the coupled two side rings for photon squeezing system is proposed. There are two forms of the coupling energies when photons travel around the micro -ring resonator that it is coupled by the two nonlinear side rings. They are the external disturbances known as the construction(creation, ̂ ) and destruction (annihilation, ̂) energy operators, which can disturb the traveling photons on the nonlinear microring resonator, from which the nonlinear behaviour calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Electromagnetically, as the electric field propagates along the ring resonator, the fundamental relations amongst the incident field, E1, transmitted field, E2, and circulating fields E3, E4 of a single resonator are inferred by combining the relations for the coupler with that of the feedback path [8]. In the spectral domain as depicted in Figure 2, the electric field propagates to the the coupling region corresonding to the source of field through the subsequent unitary matrix is given by;…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromagnetically, as the electric field propagates along the ring resonator, the fundamental relations amongst the incident field, E1, transmitted field, E2, and circulating fields E3, E4 of a single resonator are inferred by combining the relations for the coupler with that of the feedback path [8]. In the spectral domain as depicted in Figure 2, the electric field propagates to the the coupling region corresonding to the source of field through the subsequent unitary matrix is given by;…”
Section: Methodsmentioning
confidence: 99%
“…where the lumped self-and cross-coupling coefficient, r and t are assumed to be autonomous of frequency and fulfill the relations of r 2 + t 2 =1 [8]. If the feedback path (of length, 2 ) connects the output from port 4 backward into input port 3 where the electric field is stated by…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ali et al [5] have shown that the squeezed coherent light (photon) within the conventional microring resonator can be categorized to be 4 types, in which the key effect was the coupling control of the two side rings. The squeezed light beams are obtained when the uncertainty value ( ΔE ⋅ Δt ) is saturated [6]. Light fidelity (LiFi) network has become the promising technique for modern network technology [7][8][9], where the advantage over the wire (cable) network due to the more transmitted data capacity than the wire (cable) network.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast light has been successfully implemented and useful in many applications, where none of them has been used in a nanoelectronics regime. The use of fast light for fast switching time was reported, from which the system was the nonlinear ring resonator, which is called a panda ring resonator.…”
Section: Introductionmentioning
confidence: 99%